PENGARUH PENGETAHUAN KEWIRAUSAHAAN TERHADAP INTENSI BERWIRAUSAHA DENGAN DIMEDIASI VARIABEL SELF EFFICACY - Siti Sri Rahayu; Ikaputera Waspada; Ani Pinayani (Pendidikan Ekonomi FPEB Universitas Pendidikan Indonesia, 2021)
This research is motivated by issue the low intention of grade vocational school student entrepreneurship as evidence by the data of Center Statistic Unemployment Open 2018 Grade Vocational School Student more dominate of the data graduate school or college, and then reinforced with the data pre-research shows that entrepreneurship intentions grade vocational school student Cimahi City is still low. The aim of this research is knowing the effect of entrepreneurial knowledge toward entrepreneurial intentions, the effect of entrepreneurial knowledge toward self-efficacy and the effect of entrepreneurial knowledge on entrepreneurship intentions of intervening variable self-efficacy. The method used in this research is explanatory research using questionnaire as data collecting tool. Object this research is entrepreneurial knowledge, self-efficacy, and entrepreneurial intention. While the subject of this study were student of class XII Grade Vocational School Students in Cimahi City with a sample of 324 students. Data analysis technique used is Causal Step Strategy and Sobel Test. The result of this research show that: (1) entrepreneurial knowledge positively takes effect entrepreneurial intentions (2) entrepreneurial knowledge positively takes effect self-efficacy (3) entrepreneurial knowledge positively takes effect entrepreneurial intentions of intervening variable self-efficacy.